Information for contributors and readers for issue 2-2019 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2019)
CEON, the SCIndex team and the Military Technical Courier Editorial Office are glad to announce the beginning of the reviewer evaluation process for honouring the Reviewer of the Year Award and the Outstanding Reviewer Recognition. The assessment is technically supported only for the reviewers of the articles edited online through the ASSISTANT e-editing system, consistently and fully applied by the Military Technical Courier. All Military Technical Courier reviewers meet this necessary requirement.